Stress Coping Strategies among Adolescents Who Are Victims of Bullying in Vocational High Schools: A Qualitative Descriptive Approach - Azijah Tussolihah Siregar; Malim Soleh Rambe; Laila Kalsum Hasibuan (Pustaka Edukasi: Jurnal Pendidikan Indonesia, 2025)
Bullying is a form of violence that often occurs in schools and has a significant impact on the psychological condition of adolescents. This study aims to analyze the stress coping strategies used by adolescent victims of bullying and the role of social support in helping them overcome emotional pressure. This study used a descriptive qualitative approach involving two respondents who experienced verbal and physical bullying at SMK Negeri 1 Kotanopan, North Sumatra. Data were collected through in-depth interviews, observations, and documentation, then analyzed using Braun & Clarke's thematic analysis technique. The results showed that respondents used different coping strategies based on their subjective assessment of the situation. The first respondent used emotion-focused coping more because they felt unable to change the situation, while the second respondent tended to apply problem-focused coping by confronting the perpetrators and seeking help. Social support from guidance counselors, homeroom teachers, and peers proved to be a protective factor that strengthened the psychological resilience of victims. This study emphasizes the importance of whole-school approach-based school interventions to create a safe environment that supports the psychosocial recovery of students who are victims of bullying. Keywords: bullying, stress coping, adolescents, social support, mental health, whole-school approach.